Extraction of cobalt(II) and iron(II) from nickel(II) solutions with nickel salts of Cyanex 272 - Eksteen, Jacques; Olivier, M.; Dorfling, C. (Gecamin, 2011)
Crude NiSO4 solutions are often produced as a product of Sherrit-based matte leach processes leading to Fe and Co contaminated solutions of NiSO4. To upgrade the quality of these solutions for either the production of NiSO4 crystals or cathodes, or precipitated Ni, the Fe and Co must be removed. Conventional processes either use pure or saponified Cyanex 272 to extract impure metal species from pregnant nickel leach solutions. These processes require the addition of an alkali like NaOH to neutralise the protons being exchanged for the different impure metal species since extraction is a strong function of pH. Hence, while removing these impurities, sodium is added instead. This limitation can be dealt with by pre-loading of Cyanex 272 with nickel prior to impurity extraction. During the extraction stage, nickel is then exchanged for the impurities instead of hydrogen and no NaOH addition is necessary, resulting in a pure nickel product. The current work focuses on the purification of a pregnant solution that consists of 1 g/L Co, 3 g/L Fe and 80 g/L Ni.The sodium additions to the product nickel solution when using pure Cyanex 272 and when using the nickel salt of Cyanex 272 were compared. All the experiments were conducted at 50 °C, an A/O ratio of 1 and by using a 20 V% Cyanex 272 solution in kerosene as diluent. Cobalt and iron were extracted up to 95% at pH values of 5 and 3.5, respectively, when using either pure Cyanex 272 or the nickel salt of Cyanex 272. For nearly complete removal of cobalt and iron, only 0.05 g/L of sodium ended up in the product solution when using the nickel salt of Cyanex 272, compared to 4 g/L of sodium when using pure Cyanex 272. A nickel loading of 8.5 g/L was sufficient to produce a high purity nickel solution.